2018
DOI: 10.1016/j.cellsig.2018.03.008
|View full text |Cite
|
Sign up to set email alerts
|

IL-7-induced phosphorylation of the adaptor Crk-like and other targets

Abstract: IL-7 is required for T cell differentiation and mature T cell homeostasis and promotes pro-B cell proliferation and survival. Tyrosine phosphorylation plays a central role in IL-7 signaling. We identified by two-dimensional electrophoresis followed by anti-phosphotyrosine immunoblotting and mass spectrometry sixteen tyrosine phosphorylated proteins from the IL-7-dependent cell line D1. IL-7 stimulation induced the phosphorylation of the proteins STI1, ATIC and hnRNPH, involved in pathways related to survival, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…This could be explained by i) a limited efficacy of nilotinib, indicating the interest of combinatorial therapies with TKI molecules that target another pathway, such as asciminib, which binds to the myristoyl pocket of ABL in BCR-ABL instead of the www.nature.com/scientificreports/ ATP-binding domain 37 ; ii) the existence in these more immature cells of BCR-ABL-independent CrkL activation pathways. For example, it has been shown that CrkL is engaged in type I interferon receptor signalling 38,39 , and is implicated in the signalling pathways of lymphoid cells (B-and T-cell receptors, IL-7…) 40,41 . However, the role of similar molecular mechanisms in CML cells is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained by i) a limited efficacy of nilotinib, indicating the interest of combinatorial therapies with TKI molecules that target another pathway, such as asciminib, which binds to the myristoyl pocket of ABL in BCR-ABL instead of the www.nature.com/scientificreports/ ATP-binding domain 37 ; ii) the existence in these more immature cells of BCR-ABL-independent CrkL activation pathways. For example, it has been shown that CrkL is engaged in type I interferon receptor signalling 38,39 , and is implicated in the signalling pathways of lymphoid cells (B-and T-cell receptors, IL-7…) 40,41 . However, the role of similar molecular mechanisms in CML cells is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…crKl encodes the crK-like protooncogene adaptor protein, and the function of crKl has been discovered to be associated with the regulation of B cells (30) and igG levels (31). However, to the best of our knowledge, there are only a few reports detailing the involvement of crKl in the pathogenesis of Sle.…”
Section: Discussionmentioning
confidence: 99%